(untitled) (Global Journal of Science Frontier Research, 2021)
This study aimed to evaluate the efficiency of oestrus synchronization and mass insemination under the action research and development intervention. For the evaluation, a total of 126 and 883 dairy cattle were taken under action research and development intervention, respectively. The result of estrus response (90%) in action research was somewhat higher than the result obtained from development intervention (87.2%). The number of AI services per conception in action research was (1.75) lower than the development interventions (2.36). The result of conception was higher (58.4%) under action research than the development intervention (42.2%). The result further revealed that both in action research and development intervention conception significantly (P